Effect of emulsions and carbendazim on storability of kinnow (Citrus deliciosa Tenore x C. nobilis Lour) (Indian Journal of Arid Horticulture, 2025)
The individual effect of wax emulsion, oil emulsion and carbendazim were found significant in prolonging the post harvest life and standard quality of kinnow fruits. The treatment of wax emulsion and carbendazim under zero energy cool chamber gave better results. At the end of storage period (28" day), the minimum PLW (7.70%), minimum TSS (11.07 %), and maximum acidity (0.83 %) were observed in the treatment of wax emulsion 12 %+carbendazim 500 ppm under zero energy cool chamber. At ambient conditions, the fruits were not much matching in quality to that of zero energy cool chamber stored fruits.
Keywords: Carbendazim; emulsion; kinnow; shelf life; ambient conditions.